Engineers in the military - Norazman, M. Nor, Lt. Kol. Ir. Dr.; Mohd Asri, M. Nor; Sayuthi, Jaafar, Lt. Kol.; Abdul Razak, Mohd Sidek (The Institution of Engineers, Malaysia, 2011)
Link to publisher’s homepage at http://www.myiem.org.my/